SAJ Ranhill Sdn Bhd / Zaqia Alwi - Alwi, Zaqia (2017)
This report is all about my originality attitude and what my Industrial Company had been shared their knowledge. Along two months, the technician are invited me out to visit the site and joined the meeting. They showed me the real of working nature. In this report, I would explain about my working experiences and activities during my internship in SAJ Ranhill Sdn. Bhd. In SAJ, I was assigned in distributions department which is to ensure that the consumer can use water without any problems and servicing the asset of their department.